P-64 Integration of the Virtual Consultant Model in a hospice setting. (19th November 2022) - Davison, Kate; Booth, Laura
Abstract : Background: The recruitment of senior doctors in palliative medicine remains challenging, particularly in remote and rural areas (Dixon, King, Matosevic, et al., 2015). A sustainable model that would facilitate expert support and guidance was sourced through the platform of telehealth. Telehealth refers to methods in which healthcare professionals communicate clinical information remotely via several different mediums (Hanlon, Daines, Campbell, et al., 2017. J Med Internet Res. 19: e172). Aims: The integration of a virtual consultant service into our hospice multidisciplinary team to provide senior medical support remotely, allowing our hospice in-patient beds to remain open. Methods: Using quality improvement principles, careful consideration of clinical governance and consultation at senior management level, the model was trialled with twice weekly multidisciplinary meetings using videoconferencing software and out of hours telephone support. Results: The model took time to embed with understandable apprehension from the team. Challenges were encountered with our technology and room acoustics. We found the new team moved through the normal stages of forming group dynamics (Tuckman, 1965. Psychol Bull. 65: 384) but perhaps more slowly than would be the case without the virtual aspect. Having the same Consultants each week for our meetings, and having a good baseline level of experience within the on-site medical team of Specialty Doctors and Advanced Nurse Practitioners were essential to the progress made. The addition of a routine 'trouble shooting' call from one of our Consultants on a Friday enhanced support going into the weekend. Over the last two years clinical confidence in the model has grown considerably and beds remain open for the local community. Conclusion: Telehealth is a growing solution to the challenges of modern healthcare (Asprec, Blinderman, Berlin, et al., 2021 J Palliat Med. 24: 1387). Advances have been driven forward by the current COVID-19 pandemic (Ahmed, Sanghvi & Yeo, 2020. BMJ Innov. 6: 253). Organisations' infrastructure needs to adapt to provide a progressive approach to the delivery of specialist palliative care (Dahlin, Coyne & Goldberg, 2019. J Palliat Care. 34: 21). More research is needed to support development of evidence-based practice in this area.